Evaluation of the Implementation of the Generic Regional Health Information System (SIKDA) Using the HOT-Fit Model Approach at Waihoka Community Health Center, Ambon City. - Hermawan Saputra; Sindang Arief Salamun; Tati Nurhayati (JURNAL KESMAS DAN GIZI (JKG), 2025)
Humans, organizations, and technology are essential components in the implementation of the Generic Regional Health Information System (SIKDA). To improve the quality of healthcare services at Waihoka Community Health Center in Ambon, it is expected that fast, precise, and accurate access to information will be available to support policy-making and decision-making in service delivery. This study is a descriptive qualitative research approach using in-depth interviews, observations, and document analysis conducted with seven informants: one key informant from SP3 of the Ambon City Health Office, two main informants (the head of Waihoka Community Health Center and the administrative head responsible for SIKDA), and four supporting informants. The research findings indicate that the implementation of the Generic Regional Health Information System (SIKDA) at Waihoka Community Health Center has not been optimal. Several challenges were identified, including performance issues, a lack of human resources, and limited facilities and infrastructure (computers) in KIA-KAB, MTBS, laboratory, dental clinic, and cashier units. Additionally, there is no official decree appointing SIKDA officers, no guideline books or standard operating procedures (SOPs) for using SIKDA, non-real-time data entry, system errors, and a lack of integration between the P-Care application and the Generic SIKDA system.